2018
DOI: 10.1155/2018/2890357
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Flow Density Measured Using Optical Coherence Tomography Angiography after iStent Insertion in Combination with Phacoemulsification in Patients with Open-Angle Glaucoma

Abstract: Purpose To evaluate changes in flow density after the implantation of a trabecular microbypass stent (iStent) in combination with cataract surgery. Methods A total of 48 eyes of 48 patients, who underwent either cataract surgery alone (cataract group) or cataract surgery with implantation of two iStent inject devices (iStent group), were prospectively included in this study. Intraocular pressure (IOP) and flow density data before and after surgery were extracted and analyzed. Results In the iStent group, the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 23 publications
0
25
0
1
Order By: Relevance
“…Furthermore, Alnawaiseh et al [ 31 ] demonstrated the improvement of the flow density of the macular and ONH after cataract surgery with iStent. In the iStent group, the mean IOP was 18.2 ± 3.3 mmHg prior to surgery and 13.2 ± 2.3 at follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Alnawaiseh et al [ 31 ] demonstrated the improvement of the flow density of the macular and ONH after cataract surgery with iStent. In the iStent group, the mean IOP was 18.2 ± 3.3 mmHg prior to surgery and 13.2 ± 2.3 at follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Others have shown medical or surgical IOP reduction to have an impact on FD (Holló ; Alnawaiseh et al. ). Likewise, an influence of the systemic circulation on FD has been observed (Alnawaiseh et al.…”
Section: Introductionmentioning
confidence: 99%
“…This might be further evidence of a synergistic relationship between iSI and phacoemulsification as suggested by several emerging studies. 20,26,27,28,29 IOP outcomes were lower for patients receiving the single procedure at 1 week, 4 weeks, 6 months, and 18 months relative to those receiving iSI. This is best explained by the fact that no patients receiving phacoemulsification alone had POAG and therefore had lower IOPs at baseline.…”
Section: Discussionmentioning
confidence: 90%